“It has not occurred to me to see a doctor for that kind of feeling”: a qualitative study of Filipina immigrants’ perceptions of help seeking for mental health problems - Melanie L. Straiton; Heloise Marie L. Ledesma; Tam T. Donnelly (BMC Women's Health, 2018)
Abstract Background Immigrant women face greater barriers to health care, especially mental health care, than non-immigrant women. However, immigrants are a heterogeneous group and bring with them a range of different personal, social, cultural and economic factors, which impact both mental health and access to care. In this study, we explored factors that influence Filipina immigrants’ perceptions of help seeking from a general practitioner for mental health problems in Norway. Method Using data from semi-structured interviews, we applied a post-colonial feminist perspective to identify factors that affect perceptions of help seeking. Results Findings indicated that a combination of the women’s beliefs and values, stigma, experiences with healthcare services in Norway and familiarity with mental health services influence perceptions of help seeking. Some factors represented structural barriers to healthcare seeking in general, while others related to mental healthcare seeking in particular. The significance of each factor varied depending on the women’s backgrounds. Conclusions Socioeconomic status, educational background, familiarity with health services and experience of mental health can influence immigrant women’s perceptions of, and barriers for, help seeking for mental health problems. There are a number of barriers to address at a structural level to improve both the propensity to seek healthcare in general, as well as mental healthcare in particular. Efforts to increase awareness of primary mental healthcare services may also help change the perception that professional help is only appropriate for serious mental health disorders.